Factors that influence the participation of Iban in business in Sarawak - Meuk, Pelpas Pog ak. (Universiti Malaysia Sarawak (UNIMAS), 2004)
The Business status of Iban community in Sarawak is low and far behind compared to other communities and it is related to economic status and social progress of the Iban people. This study is an attempt to explore the possible answers and explanation to this scenario by investigating at the factors that are likely to influence the participation of Iban in business